Archazolid A binds to the equatorial region of the c-ring of the vacuolar H+-ATPase - Bockelmann, Svenja; Menche, Dirk; Rudolph, Sven; Bender, Tobias; Grond, Stephanie; Zezschwitz, Paultheo von; Muench, Stephen P.; Wieczorek, Helmut; Huss, Markus (The journal of biological chemistry, 2010)
The macrolactone archazolid is a novel, highly specific V-ATPase inhibitor with an IC(50) value in the low nanomolar range. The binding site of archazolid is presumed to overlap with the binding site of the established plecomacrolide V-ATPase inhibitors bafilomycin and concanamycin in subunit c of the membrane-integral V(O) complex. Using a semi-synthetic derivative of archazolid for photoaffinity labeling of the V(1)V(O) holoenzyme we confirmed binding of archazolid to the V(O) subunit c. For the plecomacrolide binding site a model has been published based on mutagenesis studies of the c subunit of Neurospora crassa, revealing 11 amino acids that are part of the binding pocket at the interface of two adjacent c subunits (Bowman, B. J., McCall, M. E., Baertsch, R., and Bowman, E. J. (2006) J. Biol. Chem. 281, 31885-31893). To investigate the contribution of these amino acids to the binding of archazolid, we established in Saccharomyces cerevisiae mutations that in N. crassa had changed the IC(50) value for bafilomycin 10-fold or more and showed that out of the amino acids forming the plecomacrolide binding pocket only one amino acid (tyrosine 142) contributes to the binding of archazolid. Using a fluorescent derivative of N,N'-dicyclohexylcarbodiimide, we found that the binding site for archazolid comprises the essential glutamate within helix 4 of subunit c. In conclusion the archazolid binding site resides within the equatorial region of the V(O) rotor subunit c. This hypothesis was supported by an additional subset of mutations within helix 4 that revealed that leucine 144 plays a role in archazolid binding.